Black alumina ceramic member having improved antistatic function, and manufacturing method thereof

JP2025023781AInactive Publication Date: 2025-02-17TSJ CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023179170
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-04
Filing Date
2023-10-17
Publication Date
2025-02-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Benefits of technology

【0022】 本発明の例示的な実施形態に係る帯電防止機能が向上したブラックアルミナセラミック部材の製造方法によると、黒色ないし黒色に近い色を発現させることで、低い光反射率を有するとともに、耐薬品性、化学安定性、耐熱性、絶縁性などの優れた物性を有するブラックアルミナセラミック部材を製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025023781000001_ABST
    Figure 2025023781000001_ABST
Patent Text Reader

Abstract

To provide a black alumina ceramic member with an improved antistatic function having low light reflectance by developing a black or near-black color and to provide a method for manufacturing the same.SOLUTION: A black alumina ceramic member may be manufactured by combining 100 pts.wt. of a black alumina ceramic raw material, 56.4-76.8 pts.wt. of an additive, and 9.5-12.5 pts.wt. of a binder, wherein: the black alumina ceramic raw material may comprise 56.4-76.6 wt.% of aluminum oxide (Al2O3) and 23.4-43.6 wt.% of a coloring agent; and the coloring agent may comprise 8.0-15.0 wt.% of Co2O3, 6.0-10.0 wt.% of Fe2O3, 4.0-7.0 wt.% of TiO2, 3.4-8.0 wt.% of MnO2, 0.5-0.8 wt.% of ZnO, 1.0-2.0 wt.% of SiO2, and 0.5-0.8 wt.% of ZrO2.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a black alumina ceramic member having improved antistatic properties and a manufacturing method thereof, and more particularly, to a method for manufacturing a black alumina ceramic member having improved antistatic properties in a final product by performing a ball milling process, a stirring process, a molding process, a drying process, and a firing process under optimized conditions, thereby minimizing the defect rate due to bending, cracks, bubbles, etc., and increasing the production yield, and to a black alumina ceramic member having improved antistatic properties manufactured based on the method. [Background technology]

[0002] Photolithography is a technology that uses light to transfer and copy a desired circuit design onto a wafer. It is a very important process in the semiconductor and display manufacturing processes in which a designed pattern is formed on the wafer, and as a leading technology in semiconductor miniaturization, it is a process that requires high patterning precision.

[0003] However, the typical alumina (Al2O3) ceramic used in the manufacturing process of such semiconductors and displays is ivory or white in color, has high light reflectivity, and the finer the process, the lower the precision.

[0004] For the reasons mentioned above, there is a demand for an alumina material that is capable of absorbing light and has a black color, low insulation resistance, and high bending strength. However, not only are black alumina materials not yet commercially available in Japan, but a manufacturing method for black alumina ceramic components has also not been established.

[0005] In general, Zn-Al-Cr-Fe spinel pigments are ceramic pigments that have a wide variety of colors. 3+ , Cr 3+ , Fe 3+It is possible to manufacture ceramics that are yellow, red, or black depending on the content of. In particular, the composition that produces black colors is the α-Al2O3 solid solution of (Cr,Fe)2O3, but for high temperatures, it has been reported that (Co,Ni)O-(Cr,Fe)2O3 spinel is suitable, and the addition of Ti or Mn oxides is also used to produce black colors. There is also a method of blackening alumina by impregnating it in a vacuum atmosphere while preventing the oxidation of carbon, but the process has not yet been established and it is not yet in general use.

[0006] Japanese Patent Publication No. 6141756 (Prior Patent 1) and Korean Patent Publication No. 1168863 disclose technical details related to ceramic vacuum chucks that have low reflectivity or contain colorants, but do not disclose any specific technology that can simultaneously optimize processability and reflectivity.

[0007] As described above, the manufacturing method of the black alumina ceramic member must have the same or similar physical properties as general alumina ceramics and must express a black or nearly black color, and therefore more precise and detailed processes must be performed, but detailed conditions of the processes related thereto have not yet been generalized.

[0008] Meanwhile, when the black alumina ceramic member is applied to a wafer manufacturing device used in the semiconductor / display manufacturing process, such as a vacuum chuck or an electrostatic chuck, momentary unbalanced static electricity may be generated between the front side of the vacuum chuck or the electrostatic chuck and the back side of the wafer when the semiconductor / display wafer is chucked, and such unbalanced static electricity may cause the semiconductor wafer to slip during the process of fixing the semiconductor / display wafer. In order to solve this problem, there is an urgent need to develop a black alumina ceramic member with improved antistatic properties. Summary of the Invention [Problem to be solved by the invention]

[0009] One of the various objects of the present invention is to provide a black alumina ceramic member having low light reflectance by expressing a black or nearly black color, and a method for producing the same.

[0010] One of the various objectives of the present invention is to provide a method for manufacturing a black alumina ceramic member that can minimize sintering defects such as bending, cracks, and bubbles by optimizing detailed process conditions.

[0011] One of the various objects of the present invention is to provide a method for manufacturing a black alumina ceramic part having an improved production yield by sequentially firing steps through a stepwise heating process and a stepwise cooling process.

[0012] One of the various objectives of the present invention is to provide a black alumina ceramic component having improved antistatic properties and a manufacturing method thereof by optimizing the composition and content ratio of manufacturing raw materials and adjusting the detailed conditions of the manufacturing process using the manufacturing raw materials. [Means for solving the problem]

[0013] A method for manufacturing a black alumina ceramic member with improved antistatic function according to an exemplary embodiment of the present invention may include a raw material preparation step of combining black alumina ceramic raw materials, a ball mill step of adding an additive to the black alumina ceramic raw materials and then pulverizing them to produce black alumina ceramic powder, a stirring step of stirring the black alumina ceramic powder and a binder, a molding step of filling the stirred black alumina ceramic powder into a mold and then pressing it to form a green body, a drying step of drying the green body, and a firing step of heating the dried green body, cooling it, and firing it. In this case, in the raw material preparation step, the black alumina ceramic raw material may be manufactured by mixing 56.4 to 76.6 wt % aluminum oxide (Al2O3) and 23.4 to 43.6 wt % colorant, and the colorant may be composed of 8.0 to 15.0 wt % Co2O3, 6.0 to 10.0 wt % Fe2O3, 4.0 to 7.0 wt % TiO2, 3.4 to 8.0 wt % MnO2, 0.5 to 0.8 wt % ZnO, 1.0 to 2.0 wt % SiO2, and 0.5 to 0.8 wt % ZrO2.

[0014] The ball mill step may be performed by adding 56.4 to 76.8 parts by weight of the additive to 100 parts by weight of the black alumina ceramic raw material, and then pulverizing the mixture.

[0015] The additives may be composed of 55 to 75 parts by weight of water (H2O) and 1.4 to 1.8 parts by weight of a dispersant with respect to 100 parts by weight of the black alumina ceramic raw material.

[0016] The stirring step may be performed by adding 9.5 to 12.5 parts by weight of a binder to 100 parts by weight of the black alumina ceramic powder, and then stirring.

[0017] The binder may be composed of 9 to 11 parts by weight of PVA and 0.5 to 1.5 parts by weight of PEG with respect to 100 parts by weight of the black alumina ceramic powder.

[0018] The firing step may include a first firing step performed by increasing the temperature from 0°C to 1,390°C, a second firing step performed by maintaining the temperature at the maximum temperature of 1,390°C, and a third firing step performed by decreasing the temperature from 1,390°C to 650°C.

[0019] The first firing step may include first to fifth temperature maintaining steps in which the temperatures are maintained at 100° C., 250° C., 400° C., 800° C., and 1100° C. for specific times, respectively.

[0020] The second firing step may be carried out for 4 to 6 hours. The third firing step may include a sixth temperature maintaining step in which the temperature is maintained at 1100° C. for a specific period of time.

[0021] A black alumina ceramic member having improved antistatic properties according to an exemplary embodiment of the present invention may be manufactured by combining 100 parts by weight of a black alumina ceramic raw material, 56.4-76.8 parts by weight of an additive, and 9.5-12.5 parts by weight of a binder, and the black alumina ceramic raw material may include 56.4-76.6% by weight of aluminum oxide (Al2O3) and 23.4-43.6% by weight of a colorant, and the colorant may be composed of 8.0-15.0% by weight of Co2O3, 6.0-10.0% by weight of Fe2O3, 4.0-7.0% by weight of TiO2, 3.4-8.0% by weight of MnO2, 0.5-0.8% by weight of ZnO, 1.0-2.0% by weight of SiO2, and 0.5-0.8% by weight of ZrO2. Effect of the Invention

[0022] According to the method for manufacturing a black alumina ceramic member with improved antistatic properties according to an exemplary embodiment of the present invention, it is possible to manufacture a black alumina ceramic member that has a black or near-black color, and thus has low light reflectance and excellent physical properties such as chemical resistance, chemical stability, heat resistance, and insulating properties.

[0023] In this case, detailed process conditions for each of the raw material preparation step, ball mill step, mixing step, molding step, drying step, and sintering step included in the manufacturing method of the black alumina ceramic member with improved antistatic function can be optimized, thereby minimizing sintering defects of the black alumina ceramic member, such as bending, cracks, and bubbles.

[0024] In addition, the firing step may include a plurality of firing steps sequentially performed through a stepwise heating process and a stepwise cooling process, thereby significantly improving the physical properties and production yield of the final black alumina ceramic member.

[0025] In addition, by optimizing the composition and content of the raw materials for manufacturing the black alumina ceramic member and adjusting the temperature conditions and execution time of the firing process during the manufacturing process, the antistatic function of the final black alumina ceramic member can be significantly improved. [Brief description of the drawings]

[0026] [Figure 1] 2 is a flow chart illustrating a method for manufacturing a black alumina ceramic member having improved antistatic properties according to an exemplary embodiment of the present invention. [Diagram 2] 4 is a flow chart illustrating the firing steps of a black alumina ceramic member with improved antistatic properties according to an exemplary embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Specific embodiments of the present invention will be described below. The following detailed description is provided to facilitate a comprehensive understanding of the methods, devices, and / or systems described herein. However, this is for illustrative purposes only, and the present invention is not limited thereto.

[0028] In describing the embodiments of the present invention, if it is determined that a specific description of the known technology related to the present invention may unnecessarily obscure the gist of the present invention, the detailed description will be omitted. The terms described below are defined in consideration of their functions in the present invention, and may vary depending on the intention or practice of the user or operator. Therefore, the definition should be based on the contents throughout this specification. The terms used in the detailed description are merely for describing the embodiments of the present invention and are in no way limiting. Unless otherwise specified, expressions in the singular form include the plural form. In this description, expressions such as "include" or "comprise" are intended to refer to certain characteristics, numbers, steps, operations, elements, parts or combinations thereof, and should not be interpreted to exclude the presence or possibility of one or more other characteristics, numbers, steps, operations, elements, parts or combinations thereof other than those described.

[0029] In addition, when describing components of the embodiments of the present invention, terms such as first, second, A, B, (a), (b), etc. may be used. Such terms are merely used to distinguish the components from other components, and do not limit the essence, order, or procedure of the components.

[0030] FIG. 1 is a flow chart illustrating a method for manufacturing a black alumina ceramic member having improved antistatic properties according to an exemplary embodiment of the present invention. Referring to FIG. 1, a method for manufacturing a black alumina ceramic member with improved antistatic function according to an exemplary embodiment of the present invention may include a raw material preparation step (S1) of combining black alumina ceramic raw materials, a ball mill step (S2) of grinding the black alumina ceramic raw materials together with an additive to produce black alumina ceramic powder, a mixing step (S3) of mixing the black alumina ceramic powder with a binder, a molding step (S4) of filling the mixed black alumina ceramic powder into a mold and pressing it to form a green body, a drying step (S5) of drying the green body, and a firing step (S6) of heating, cooling, and firing the dried green body.

[0031] In an exemplary embodiment, in the raw material preparation step (S1), the black alumina ceramic raw material may be manufactured by mixing 56.4-76.6 wt % aluminum oxide (Al2O3) with 23.4-43.6 wt % colorant.

[0032] In this regard, if the content of aluminum oxide contained in the black alumina ceramic raw material is less than 56.4 wt %, the physical properties of the final black alumina ceramic member may be degraded, whereas if the content of aluminum oxide contained in the black alumina ceramic raw material is more than 76.6 wt %, the black or near black color may not be fully expressed and the light reflectance may increase.

[0033] That is, if the content of the colorant exceeds 43.6 wt %, the physical properties of the final black alumina ceramic member may be deteriorated, and if the content of the colorant is less than 23.4 wt %, the black or near black color may not be fully expressed, and the light reflectance of the final black alumina ceramic member may be increased.

[0034] In one embodiment, the colorant may be comprised of 8.0-15.0 wt.% Co2O3, 6.0-10.0 wt.% Fe2O3, 4.0-7.0 wt.% TiO2, 3.4-8.0 wt.% MnO2, 0.5-0.8 wt.% ZnO, 1.0-2.0 wt.% SiO2, and 0.5-0.8 wt.% ZrO2.

[0035] If the contents of Co2O3, Fe2O3, TiO2, and MnO2 among the components contained in the colorant are not within the above-mentioned ranges, the color expression of the manufactured black alumina ceramic member may be insufficient and the light reflectance may be increased. If the contents of Co2O3, Fe2O3, TiO2, and MnO2 among the components contained in the colorant are beyond the above-mentioned ranges, the physical properties of the manufactured black alumina ceramic member may be deteriorated.

[0036] In addition, if the content of ZnO among the components contained in the colorant does not reach or exceeds the above-mentioned range, cracks may occur in the manufactured black alumina ceramic, and if the content of ZnO among the components contained in the colorant does not reach or exceeds the above-mentioned range, the theoretical density of the manufactured black alumina ceramic member may be relatively lower than that of fine alumina ceramic, and sintering defects such as bending, cracks, and bubbles may occur.

[0037] In addition, if the content of SiO2 and ZrO2 among the components contained in the colorant does not reach or exceeds the above-mentioned numerical range, cracks may occur in the finally manufactured black alumina ceramic member, or the theoretical density of the manufactured black alumina ceramic member may be relatively lower than that of fine alumina ceramics, and sintering defects such as bending, cracks, and bubbles may occur.

[0038] After the raw material preparation step (S1) is completed, a ball mill step (S2) may be performed in which additives are added to the black alumina ceramic raw material and then the black alumina ceramic raw material is pulverized to produce black alumina ceramic powder.

[0039] In an exemplary embodiment, the ball mill step (S2) may be performed by adding 56.4 to 76.8 parts by weight of the additive to 100 parts by weight of the black alumina ceramic raw material, and then pulverizing the mixture.

[0040] In one embodiment, the additive may be composed of water (H2O) and a dispersant, and the additive may be composed of 55 to 75 parts by weight of water (H2O) and 1.4 to 1.8 parts by weight of the dispersant, and preferably 60 to 70 parts by weight of water (H2O) and 1.5 to 1.7 parts by weight of the dispersant, relative to 100 parts by weight of the black alumina ceramic raw material.

[0041] In this case, the dispersant may be added so that the black alumina ceramic raw material of the solid component and the additive of the liquid component can be sufficiently dispersed, and a dispersant containing at least one selected from the group consisting of anionic compounds, cationic compounds, nonionic compounds, and polymer compounds may be used. As the dispersant, a water-based dispersant may be used, and for example, an anionic, nonionic, polycarboxylic acid, polycarboxylic acid amine salt, polycarboxylic acid ammonium salt, polycarboxylic acid sodium salt, or polyester polyester dispersant may be used. However, the concept of the present invention is not necessarily limited to this, and as the dispersant, for example, a polyethylene oil-based dispersant may be used.

[0042] Specifically, the ball mill step (S2) may be performed by feeding aluminum oxide or alumina (Al2O3) balls produced in the raw material preparation step (S1), i.e., balls made of the black alumina ceramic raw material, into a ball mill device in a volume of 50% to 70% of the ball mill device, further feeding the additives in the remaining volume of the ball mill device, and then setting the driving rpm of the ball mill device to 45 rpm to 55 rpm, preferably 48 rpm, and driving the ball mill device.

[0043] In an exemplary embodiment, the particle size of the black alumina ceramic powder produced in the ball mill step (S2) may be 0.109 μm to 0.153 μm. In this case, if the particle size of the black alumina ceramic powder is smaller than 0.109 μm, the physical properties of the finally produced black alumina ceramic member may be deteriorated, and if the particle size of the black alumina ceramic powder is larger than 0.153 μm, the light reflectance of the finally produced black alumina ceramic member may be high or sintering defects such as bending, cracks, bubbles, etc. may occur.

[0044] In an exemplary embodiment, the ball milling step (S2) may be performed by driving the ball milling device for 15 to 20 hours. In this case, if the driving time of the ball milling device is less than 15 hours, the physical properties of the finally manufactured black alumina ceramic member may be deteriorated, and if the driving time of the ball milling device is more than 20 hours, the light reflectance of the finally manufactured black alumina ceramic member may be high or sintering defects such as bending, cracks, and bubbles may occur.

[0045] After the ball milling step (S2) is completed, a mixing step (S3) of mixing the black alumina ceramic powder with a binder, a molding step (S4) of filling the mixed black alumina ceramic powder into a mold and pressing it to form it, and a drying step (S5) of drying the black alumina molded body may be sequentially performed.

[0046] The stirring step (S3) may be performed by mixing the black alumina ceramic powder and the binder, then putting the mixture into a pressure tank, and driving an agitator installed in the pressure tank at 30 rpm for 48 hours.

[0047] In an exemplary embodiment, the stirring step (S3) may be performed by adding 9.5 to 12.5 parts by weight of a binder to 100 parts by weight of the black alumina ceramic powder, followed by stirring. In one embodiment, the binder may be composed of 9 to 11 parts by weight of PVA and 0.5 to 1.5 parts by weight of PEG to 100 parts by weight of the black alumina ceramic powder.

[0048] The molding step (S4) may be performed by assembling a mold that meets the specifications, tilting the mold by 45°, setting the pressure of the pressure tank to 3 kg / MPa, filling the mold with black alumina ceramic powder mixed with the binder, maintaining the mold horizontal, and after 48 hours, separating the molded body from the mold and then naturally drying it for 24 hours.

[0049] The drying step (S5) may be performed by carrying out a constant temperature and humidity drying step of drying the naturally dried molded body for 10 to 15 days in a constant temperature and humidity drying chamber set under conditions of an internal humidity of 80% and an internal temperature of 28°C, and then carrying out a thermal drying step of drying the molded body after the constant temperature and humidity drying for 2 to 3 days in a thermal drying chamber set under internal temperature conditions of 40°C to 50°C.

[0050] In this case, the constant temperature and humidity drying step and the heat drying step may be performed sequentially. After the drying step (S5), a firing step (S6) may be performed. The overall process of the firing step (S6) is as shown in Table 1 below.

[0051] [Table 1]

[0052] FIG. 2 is a flow chart illustrating the firing steps of a black alumina ceramic member according to an exemplary embodiment of the present invention. Referring to FIG. 2 together with Table 1, the firing step (S6) may include a first firing step (S61) performed by gradually increasing the temperature from 0° C. to 1,390° C., a second firing step (S62) performed by maintaining the temperature at the maximum temperature of 1,390° C., and a third firing step (S63) performed by gradually decreasing the temperature from 1,390° C. to 650° C. The first firing step (S61) may include a first temperature rise section for increasing the temperature from 0°C to 100°C, a second temperature rise section for increasing the temperature from 100°C to 250°C, a third temperature rise section for increasing the temperature from 250°C to 400°C, a fourth temperature rise section for increasing the temperature from 400°C to 800°C, a fifth temperature rise section for increasing the temperature from 800°C to 1,100°C, and a sixth temperature rise section for increasing the temperature from 1,100°C to 1,390°C.

[0053] The first temperature rise section may be performed for about 24 hours, the second temperature rise section may be performed for about 96 hours, and the third temperature rise section may be performed for about 120 hours, the fourth temperature rise section may be performed for about 96 hours, the fifth temperature rise section may be performed for about 48 hours, and the sixth temperature rise section may be performed for about 30 hours.

[0054] The first heating section may be a section for increasing moisture, the second heating section may be a section for degreasing the dispersant, and the third heating section may be a section for degreasing the additive components. The fourth heating section may be a section for oxidizing and removing carbon or carbon components, the fifth heating section may be a section for primary contraction of the product, and the sixth heating section may be a section for secondary contraction of the product. In this case, the fifth heating section may be referred to as a first contraction step, and the sixth heating section may be referred to as a second contraction step.

[0055] The first baking step (S61) may further include a temperature maintaining step of maintaining the temperature for a certain period of time between the first temperature increasing section to the sixth temperature increasing section. In an exemplary embodiment, a first temperature maintenance step may be performed between the first and second heating sections, maintaining a temperature of about 100° C. for about 2 hours, a second temperature maintenance step may be performed between the second and third heating sections, maintaining a temperature of about 250° C. for about 2 hours, a third temperature maintenance step may be performed between the third and fourth heating sections, maintaining a temperature of about 400° C. for about 4 hours, a fourth temperature maintenance step may be performed between the fourth and fifth heating sections, maintaining a temperature of about 800° C. for about 2 hours, and a fifth temperature maintenance step may be performed between the fifth and sixth heating sections, maintaining a temperature of about 1,100° C. for about 2 hours. After the sixth heating section, a second firing step (S62) may be performed by maintaining the temperature at the maximum temperature of 1,390° C.

[0056] In this case, the first temperature maintaining section may be a section for forming an internal line of the compact, the second temperature maintaining section may be a section for degreasing the dispersant and forming an overall line, the third temperature maintaining section may be a section for removing a residual binder, the fourth temperature maintaining section may be a section for removing a residual carbon or a carbon component, and the fifth temperature maintaining section may be a section for further smoothly progressing the primary shrinkage of the product. In this case, the third temperature maintaining section may be referred to as a binder removing step.

[0057] The second baking step (S62) may be a section for completing secondary shrinkage of the product and perfecting the physical properties of the product. Meanwhile, when the firing step is performed at a temperature of 1,400°C or more, which is set as the conventional maximum temperature, when the finally manufactured black alumina ceramic member is applied to a wafer chuck for manufacturing semiconductors / displays, a problem has been found in that static electricity is generated and the antistatic function is reduced. In order to solve this problem, a process of adjusting the maximum temperature in the firing step (S6) according to the present invention has been performed, and through various maximum temperature deformation experiments, it has been set to 1,390°C as the maximum temperature at which the antistatic function of the finally manufactured black alumina ceramic member is most improved and the production yield can be increased.

[0058] As a result, although the difference between the conventional peak temperature and the peak temperature of the present invention is only 10°C, which is not a large temperature difference, it was confirmed that there was a large difference in the antistatic function and production yield of the finally manufactured black alumina ceramic member due to the fact that the temperature is not immediately lowered from the peak temperature and the second firing step (S62) is performed to maintain the temperature for a specific period of time, and the specific experimental results are shown in Table 2 below.

[0059] [Table 2]

[0060] In this case, the embodiment of the present invention is a vacuum chuck using a ceramic member manufactured by applying the composition and content ratio of the manufacturing raw materials described above and setting the maximum firing temperature to 1,390 ° C., and Comparative Example 1 is a vacuum chuck using a ceramic member manufactured by applying the composition and content ratio of the manufacturing raw materials similar to those of the embodiment, but setting the maximum firing temperature to 1,400 ° C. Comparative Examples 2 to 3 are vacuum chucks using a ceramic member manufactured by setting the maximum firing temperature to 1,390 ° C. as in the embodiment, but using a composition and content ratio of the manufacturing raw materials different from those of the embodiment. Specifically, Comparative Example 2 is a vacuum chuck manufactured based on the recipe for Black Ceramic (JP7242699 B2) manufactured by Kyocera Co., Ltd. of Japan, and Comparative Example 3 is a vacuum chuck manufactured based on the recipe for the manufacturing method of black alumina ceramic (KR 2023-0064673 A) of the same company. Comparative Example 4 is a vacuum chuck using a ceramic member manufactured by applying the same composition and content ratio of the manufacturing raw materials as in the above-mentioned Example, setting the maximum firing temperature to 1,390°C, and performing the second heating section, the third heating section, and the fourth heating section for 48 hours, 96 hours, and 48 hours, respectively.

[0061] As shown in Table 2, it was confirmed that Comparative Examples 1 to 4 had higher surface resistance values ​​than the examples of the present invention, and therefore it was confirmed that the antistatic function of the vacuum chuck using the ceramic members finally manufactured according to the examples of the present invention was significantly improved.

[0062] After the first firing step (S61) and the second firing step (S62) are completed, a third firing step (S63) may be performed by lowering the temperature from 1,390°C to 650°C.

[0063] The third firing step (S63) may include a first temperature decreasing section in which the temperature is decreased from 1,390°C to 1,100°C, and a second temperature decreasing section in which the temperature is decreased from 1,100°C to 650°C, and a sixth temperature maintaining step in which the temperature of 1,100°C is maintained for about 1 hour may be performed between the first temperature decreasing section and the second temperature decreasing section. In this case, the sixth temperature maintaining step may be a section for suppressing stress generation due to rapid cooling of the product.

[0064] After the firing step (S6) is performed, the processing step (S7) may be performed in various ways depending on the purpose, use, function, etc. of the final product, and when the processing step (S7) is completed, the manufacture of the black alumina ceramic part can be completed.

[0065] As described above, the method for manufacturing a black alumina ceramic member according to an exemplary embodiment of the present invention may include a raw material preparation step (S1), a ball mill step (S2), a stirring step (S3), a molding step (S4), a drying step (S5), and a firing step (S6). Since detailed process conditions for each step can be optimized, a black alumina ceramic having a black or nearly black color and low light reflectance as well as excellent physical properties such as chemical resistance, chemical stability, heat resistance, and insulation can be manufactured, and sintering defects such as bending, cracks, and bubbles in the finally manufactured black alumina ceramic member can be minimized.

[0066] In particular, the firing step (S6) may include a plurality of firing steps sequentially performed through a stepwise heating process and a stepwise cooling process, thereby significantly improving the production yield of the black alumina ceramic member.

[0067] In addition, by optimizing the composition and content of the raw materials for manufacturing the black alumina ceramic member and adjusting the temperature conditions and execution time of the firing process during the manufacturing process, the antistatic function of the final black alumina ceramic member can be significantly improved.

[0068] However, the concept of the present invention is not necessarily limited thereto, and the method according to the exemplary embodiment of the present invention may be applied to various products / technical fields in addition to those mentioned above.

[0069] Although various embodiments of the present invention have been described in detail above, those skilled in the art will understand that various modifications can be made to the above-described embodiments without departing from the scope of the present invention. Therefore, the scope of the present invention should not be limited to the described embodiments, but should be determined not only by the claims below, but also by equivalents to the claims.

Claims

1. A raw material preparation step of combining black alumina ceramic raw materials; a ball mill step of adding an additive to the black alumina ceramic raw material and then pulverizing the black alumina ceramic raw material to produce a black alumina ceramic powder; a stirring step of stirring the black alumina ceramic powder and a binder; a molding step of filling the stirred black alumina ceramic powder into a mold and then pressing the molded body; A drying step of drying the molded body; A firing step of heating the dried molded body, then cooling and firing the molded body, In the raw material preparation step, the black alumina ceramic raw material is 56.4 to 76.6 wt % aluminum oxide (Al 2 O 3 ) and 23.4 to 43.6% by weight of a colorant, The colorant contains 8.0 to 15.0 wt % Co. 2 O 3 , 6.0 to 10.0 wt.% Fe 2 O 3 , 4.0 to 7.0 wt.% TiO 2 , 3.4 to 8.0% by weight of MnO 2 , 0.5 to 0.8 wt. % ZnO, 1.0 to 2.0 wt. % SiO 2 %, and 0.5 to 0.8 wt. % ZrO 2 A method for producing a black alumina ceramic member having improved antistatic properties, comprising:

2. 2. The method for producing a black alumina ceramic member having improved antistatic properties according to claim 1, wherein the ball mill step is performed by adding 56.4 to 76.8 parts by weight of the additive to 100 parts by weight of the black alumina ceramic raw material and then pulverizing the mixture.

3. The additive is water (H 2 3. The method for producing a black alumina ceramic member having improved antistatic properties according to claim 2, characterized in that the composition comprises 55 to 75 parts by weight of the binder and 1.4 to 1.8 parts by weight of a dispersant.

4. 2. The method for producing a black alumina ceramic member having improved antistatic properties according to claim 1, wherein the stirring step is performed by adding 9.5 to 12.5 parts by weight of a binder to 100 parts by weight of the black alumina ceramic powder and then stirring the mixture.

5. 2. The method for manufacturing a black alumina ceramic member having improved antistatic properties according to claim 1, wherein the binder is composed of 9 to 11 parts by weight of PVA and 0.5 to 1.5 parts by weight of PEG, based on 100 parts by weight of the black alumina ceramic powder.

6. The baking step includes: A first firing step carried out by increasing the temperature from 0° C. to 1,390° C.; A second firing step is performed by maintaining the temperature at a maximum temperature of 1,390°C.

2. The method for manufacturing a black alumina ceramic member having improved antistatic function according to claim 1, further comprising: a third firing step, the third firing step being carried out by decreasing the temperature from 1,390°C to 650°C.

7. The first firing step comprises: The method for manufacturing a black alumina ceramic member having improved antistatic properties according to claim 6, further comprising first to fifth temperature maintaining steps for maintaining the temperatures at 100°C, 250°C, 400°C, 800°C, and 1100°C for specific periods of time, respectively.

8. 7. The method for manufacturing a black alumina ceramic member having improved antistatic properties according to claim 6, wherein the second firing step is performed for 4 to 6 hours.

9. The third firing step is 7. The method for manufacturing a black alumina ceramic member having improved antistatic properties as claimed in claim 6, further comprising a sixth temperature maintaining step of maintaining the temperature at 1100° C. for a specific period of time.

10. 100 parts by weight of black alumina ceramic raw material; 56.4 to 76.8 parts by weight of an additive; and 9.5 to 12.5 parts by weight of a binder; The black alumina ceramic raw material is 56.4 to 76.6% by weight of aluminum oxide (Al 2 O 3 )and, 23.4 to 43.6% by weight of a colorant; The colorant contains 8.0 to 15.0 wt % Co. 2 O 3 , 6.0 to 10.0 wt.% Fe 2 O 3 , 4.0 to 7.0 wt.% TiO 2 , 3.4 to 8.0% by weight of MnO 2 , 0.5 to 0.8 wt. % ZnO, 1.0 to 2.0 wt. % SiO 2 %, and 0.5 to 0.8 wt. % ZrO 2 A black alumina ceramic member having an improved antistatic function, characterized in that it is composed of: